2016
DOI: 10.1186/s40294-016-0030-y
|View full text |Cite|
|
Sign up to set email alerts
|

A survey on MAC protocols for complex self-organizing cognitive radio networks

Abstract: Complex self-organizing cognitive radio (CR) networks serve as a framework for accessing the spectrum allocation dynamically where the vacant channels can be used by CR nodes opportunistically. CR devices must be capable of exploiting spectrum opportunities and exchanging control information over a control channel. Moreover, CR nodes should intelligently coordinate their access between different cognitive radios to avoid collisions on the available spectrum channels and to vacate the channel for the licensed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…The behavior and interactions of the SUs in the course of the channel sharing is well analyzed through a noncooperative, cooperative, and mixed strategic games for which the Nash equilibrium and the Nash bargaining solution is also derived. Further, an extensive study and survey of medium access protocols in CRNs can be found in Gavrilovska et al and Shah et al Various medium access protocols have been divided into two groups, namely, distributed and centralized. While in the distributed approach, each node decides on its own or through cooperation to transmit; a secondary base station decides on the SU that can access the channel in the centralized approach.…”
Section: Channel Assignment In Literaturementioning
confidence: 99%
“…The behavior and interactions of the SUs in the course of the channel sharing is well analyzed through a noncooperative, cooperative, and mixed strategic games for which the Nash equilibrium and the Nash bargaining solution is also derived. Further, an extensive study and survey of medium access protocols in CRNs can be found in Gavrilovska et al and Shah et al Various medium access protocols have been divided into two groups, namely, distributed and centralized. While in the distributed approach, each node decides on its own or through cooperation to transmit; a secondary base station decides on the SU that can access the channel in the centralized approach.…”
Section: Channel Assignment In Literaturementioning
confidence: 99%
“…The use of a common control channel (CCC) is one widely adopted rendezvous approach in the literature. [1][2][3] However, this approach has many drawbacks. A CCC is susceptible to early saturation by SUs, long-time blocking by PUs, or jamming by attackers.…”
Section: Motivationmentioning
confidence: 99%
“…The use of a common control channel (CCC) is one widely adopted rendezvous approach in the literature . However, this approach has many drawbacks.…”
Section: Introductionmentioning
confidence: 99%